Alveolar Ridge Preservation Using Xenogeneic Collagen Matrix and Bone Allograft - Andreas O. Parashis; Charalampos J. Kalaitzakis; Dimitris N. Tatakis; Konstantinos Tosios (Hindawi Limited, 2014)
Alveolar ridge preservation (ARP) has been shown to prevent postextraction bone loss. The aim of this report is to highlight the clinical, radiographic, and histological outcomes following use of a bilayer xenogeneic collagen matrix (XCM) in combination with freeze-dried bone allograft (FDBA) for ARP. Nine patients were treated after extraction of 18 teeth. Following minimal flap elevation and atraumatic extraction, sockets were filled with FDBA. The XCM was adapted to cover the defect and 2-3 mm of adjacent bone and flaps were repositioned. Healing was uneventful in all cases, the XCM remained in place, and any matrix exposure was devoid of further complications. Exposed matrix portions were slowly vascularized and replaced by mature keratinized tissue within 2-3 months. Radiographic and clinical assessment indicated adequate volume of bone for implant placement, with all planned implants placed in acceptable positions. When fixed partial dentures were placed, restorations fulfilled aesthetic demands without requiring further augmentation procedures. Histological and immunohistochemical analysis from 9 sites (4 patients) indicated normal mucosa with complete incorporation of the matrix and absence of inflammatory response. The XCM + FDBA combination resulted in minimal complications and desirable soft and hard tissue therapeutic outcomes, suggesting the feasibility of this approach for ARP.